Simulation and Practical Realization of A 24-Pair Electronic Continuity Test Circuit for MSAN ZTE - Ghouali, Samir; Moulay, Mohammed; Feham, Mohammed (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2019)
The continuity test of a telephone line is a technique used very often by every Telecom site engineer. Continuity refers to communication that does not face any interruption. Very often, the continuity measurement takes place during troubleshooting to ensure that the lines are intact. The work presented in this paper is based on the principle of MDF continuity rule lines for MSAN site. It presents the practical realization of a continuity tester circuit to verify several telephone lines simultaneously, specifically 24 pairs (24 subscribers) at the same time. Our solution suggested for making troubleshooting in one of the outages/ malfunctions more flexible and fluid in terms of intervention and time for repair. A case study involving 18 sites in two different regions in Algeria, Constantine (without circuit) and El Oued (with circuit) was conducted and the results showed there was a gain ratio estimated at about 338/1361 (Min).